Disrupted Brain Functional Network Topology in Essential Tremor Patients With Poor Sleep Quality - Peng, Jiaxin; Yang, Jing; Li, Junying; Lei, Du; Li, Nannan; Suo, Xueling; Duan, Liren; Chen, Chaolan; Zeng, Yan; Xi, Jing; Jiang, Yi; Gong, Qiyong; et al. (Frontiers in Neuroscience, 2022)
Sleep disturbances, especially poor sleep quality (QoS), are common among essential tremor (ET) patients and may have adverse effects on patients' quality of life, but the etiology driving the poor QoS in these individuals remains inadequately understood. Few data are available on the neuro-imaging alterations of ET with poor QoS. Thirty-eight ET patients with poor QoS (SleET), 48 ET patients with normal QoS (NorET), and 80 healthy controls (HCs) participated in our study. All subjects underwent a 3.0-Tesla magnetic resonance imaging (MRI) scan for resting-state functional MRI data collection. Then, the whole-brain functional connectome was constructed by thresholding the partial correlation matrices of 116 brain regions, and graph theory and network-based statistical analyses were performed. We used a non-parametric permutation test for group comparisons of topological metrics. Partial correlation analyses between topographic features and clinical characteristics were conducted. The SleET and NorET groups exhibited decreased clustering coefficients, global efficiency, and local efficiency and increased characteristic path length. Both of these groups also showed reduced nodal degree and nodal efficiency in the left superior dorsolateral frontal gyrus, superior frontal medial gyrus (SFGmed), posterior cingulate gyrus, lingual gyrus, superior occipital gyrus, right middle occipital gyrus, and right fusiform gyrus. The SleET group additionally presented reduced nodal degrees and nodal efficiency in the right SFGmed relative to the NorET and HC groups, and nodal efficiency in the right SFGmed was negatively correlated with the Pittsburgh Sleep Quality Index score. The observed impaired topographical organizations of functional brain networks within the central executive network, default mode network, and visual network serve to further our knowledge of the complex interactions between tremor and sleep, adding to our understanding of the underlying neural mechanisms of ET with poor QoS.